2004
DOI: 10.1111/j.0889-7204.2004.02267.x
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Cardiovascular Disease Risk in Midlife Immigrant Women From the Former Soviet Union

Abstract: This study examines relationships among acculturation, depression, and cardiovascular risk factors in midlife women from the former Soviet Union and identifies factors predicting Framingham Risk Scores. Data were collected at baseline and 1 year later from 218 participants in a longitudinal study of postimmigration health. The leading risk factors were obesity, dyslipidemia, and depression. Older women had lower American Behavioral Acculturation subscale scores, higher Russian Behavioral Acculturation subscale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…We show the most prevalent religion among immigrants and first language based on the region of birth to facilitate the grouping of immigrants and the interpretation of potential acculturation barriers. Four of the studies 12,14,15,16 used only female samples. All but one of the studies 17 sampled only adults.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We show the most prevalent religion among immigrants and first language based on the region of birth to facilitate the grouping of immigrants and the interpretation of potential acculturation barriers. Four of the studies 12,14,15,16 used only female samples. All but one of the studies 17 sampled only adults.…”
Section: Resultsmentioning
confidence: 99%
“…BMI was self-reported in the majority of the studies. Ten of the studies measured weight and height 14,16,18,20,21,22,23,24 , while one study measured only height and weight was self-reported 25 . In another study, weight and height were measured but change in BMI (outcome variable) was calculated based on self-reported past weight and height 26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, while there is limited research investigating gender differences in the association between BMI and acculturation, Lee and colleagues found no significant relationship between acculturation and obesity in their female sub-sample [19]. Other studies have found negative or mixed associations, including less obesity in migrant women [20-22]. This observation reinforces the argument that, in all likelihood, a complex interaction between culture, ethnicity, gender and place of origin impacts on a range of health-related factors, including obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Further, while there is limited research investigating gender differences in the association between BMI and acculturation, Lee and colleagues found no significant relationship between acculturation and obesity in their female sub-sample [19]. Other studies have found negative or mixed associations, including less obesity in migrant women [20][21][22]. This observation reinforces the argument that, in all likelihood, a complex interaction between culture, ethnicity, gender and place of origin impacts on a range of health-related factors, including obesity.…”
Section: Introductionmentioning
confidence: 97%